Answer:
Step-by-step explanation:
The answer is C, the range changes from (y | y > 0) to (y | y > 2)
sorry if i am wrong
Option 2:
is the correct answer.
Step-by-step explanation:
The radical expressions like these are simplified by using fractional exponents
given
![\frac{\sqrt{4}}{\sqrt[3]{4} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B4%7D%7D%7B%5Csqrt%5B3%5D%7B4%7D%20%7D)
Converting radicals into exponents
When there is no base the exponent is 1/2 and as the base is 3, the exponent will be 1/3
So
![=\frac{4^{\frac{1}{2}}}{4^{\frac{1}{3}}}](https://tex.z-dn.net/?f=%3D%5Cfrac%7B4%5E%7B%5Cfrac%7B1%7D%7B2%7D%7D%7D%7B4%5E%7B%5Cfrac%7B1%7D%7B3%7D%7D%7D)
As the bases of numerator and denominator is same, the exponents can be subtracted
![=4^{\frac{1}{2}-\frac{1}{3}}\\=4^{\frac{3-2}{6}}\\=4^{\frac{1}{6}}](https://tex.z-dn.net/?f=%3D4%5E%7B%5Cfrac%7B1%7D%7B2%7D-%5Cfrac%7B1%7D%7B3%7D%7D%5C%5C%3D4%5E%7B%5Cfrac%7B3-2%7D%7B6%7D%7D%5C%5C%3D4%5E%7B%5Cfrac%7B1%7D%7B6%7D%7D)
Hence,
Option 2:
is the correct answer.
Keywords: Exponents, radicals
Learn more about radicals at:
#LearnwithBrainly
Answer:
See explanation, and ask for more details if unclear!
Step-by-step explanation:
The perfect square of this equation is
, since the square would be
. 1/4=4/16, meaning that you can set up the equation in the following way:
![(x^2-x+\frac{1}{4})-\frac{1}{16}=0](https://tex.z-dn.net/?f=%28x%5E2-x%2B%5Cfrac%7B1%7D%7B4%7D%29-%5Cfrac%7B1%7D%7B16%7D%3D0)
![(x-\frac{1}{2})^2=\frac{1}{16}](https://tex.z-dn.net/?f=%28x-%5Cfrac%7B1%7D%7B2%7D%29%5E2%3D%5Cfrac%7B1%7D%7B16%7D)
Take the square root of both sides:
![x-\frac{1}{2}=\pm \frac{1}{4}](https://tex.z-dn.net/?f=x-%5Cfrac%7B1%7D%7B2%7D%3D%5Cpm%20%5Cfrac%7B1%7D%7B4%7D)
Add 1/2 to both sides:
. Hope this helps!
Answer:
(4, - 2 )
Step-by-step explanation:
Given the 2 equations
x + y = 2 → (1)
x - y = 6 → (2)
Adding the 2 equations term by term will eliminate the term in y, that is
(x + x) + (y - y) = (2 + 6)
2x = 8 ( divide both sides by 2 )
x = 4
Substitute x = 4 in either of the 2 equations and solve for y
Substituting in (1)
4 + y = 2 ( subtract 4 from both sides )
y = - 2
Solution is (4, - 2 )
Answer:
144:9
16
16 ft high
Step-by-step explanation:
Easy...could also be written as 144/9 or 144 to 9
Divide
Same thing
Hope this helps. Have a nice day